Analisis Sifat Fisik Dan Mekanik Akibat Variasi Temperatur Uji Pada Komposit Serat Batang Pohon Pisang Yang Disusun 5 Lapis Dengan Orientasi Serat (-30/60/0/-30/60) - Wijanarno, Agung; , Ir. Ngafwan, MT; , Ir. Masyrukan, MT (2015)
This study aimed to describe the tensile strength and bending strength of the composite fibers are arranged banana trees 5 layers with fiber arrangement -30 / 60/0 / -30 / 60 and describe macro picture after the tensile test and bending due to changes temperature. The initial process pelupasan and cutting tree bark pisang.Proses immersion for 1 month followed pengerokan and brushing using a metal plate to exit seratnya.Penjemuran cool, dry place until the next washing process using a chemical solution of 5% potassium permangant per 1 liter of distilled water for 2 jam.penjemuran under the sun to dry resumed process oven until the moisture content is constant. Composite manufacturing methods Hand Lay-up, using fiber weight fraction ratio of 30% and fiber orientation -30 / 60/0 / -30 / 60. Using a tensile test ASTM D 3039 standard and bending tests using standard ASTM D7269 with a temperature variation of 29 0C and temperature test 350C, 450C and 55 0C, and describes the tensile strength and bending as well as macro image of composite polyester fiber banana trees due changes in temperature. The test results concluded that the higher the temperature test the tensile strength is getting weaker or down, this proved to be the tensile strength decreased from 26.4 N / mm2 to 20.3 N / mm2 and the temperaruji higher bending test, the test voltage values the higher the bending is evident that the increase in value of the voltage dari0,278 N / mm2 to 7.08 N / mm2 .At visible results macro photo fault structure has the properties of clay composite specimens.